We hardly need to use our ears: Video, audio and the shaping of the podcast medium in the 2020s. - Berry, Richard (Radio Journal: International Studies in Broadcast & Audio Media, 2024)
In 1979, the British pop band The Buggles released 'Video Killed the Radio Star', generating a provocation used to explain change (where x killed y). Two years later, the song's video was used to launch MTV, marking a change in how audiences consumed music. It is not the title that is of interest here, but a line in the track that suggests in the age of video, that we no longer need to use our ears. Although the open standard of podcasting has meant that video and audio could coexist, podcasting has been primarily an auditory medium. However, in 2024, several leading podcasts on Spotify now play as easily as video as audio. This article discusses this evolution, arguing that this shift not only reflects the actors that shape podcasting but also poses questions for how we might define podcasting in its third decade. Is podcasting still an aural medium?